Zur unregelmäßigen Flexion der ungarischen Verben megy und van - Holst, Jan Henrik (Suomalais-Ugrilaisen Seuran Aikakauskirja, 2015)
The two Hungarian verbs megy ʻto goʼ and van ʻto beʼ exhibit irregular forms in the present indicative. This article presents a theory on which diachronic causes may lie behind the data: forms of the imperative were taken over into the indicative, and the paradigms underwent further restructuring. Section 1 discusses the problem, section 2 the verb megy, section 3 the verb van, section 4 further issues concerning both verbs and section 5 final considerations.